Challenges in building a brand image for entrepreneurial-based vocational institutions : a case study of Wilmar Business Indonesia Polytechnic - Jessica, Jessica; Tryana, Meilita; Fitri, Isnen (Jurnal Mantik, 2025)
In the era of growing competition among higher education institutions, vocational colleges must build a distinctive brand image that highlights entrepreneurship. Wilmar Business Indonesia Polytechnic (WBI) in Medan represents a case of how vocational institutions develop an entrepreneurial-based brand identity. Although every institution has its own uniqueness, challenges often arise in communicating it effectively to the public. This study aims to analyze the challenges faced by WBI in shaping an entrepreneurial brand image as a vocational institution. Building such an image requires consistent communication strategies, adequate resources, and public understanding of vocational education. Using a qualitative descriptive method, data were obtained through interviews, observations, and documentation involving management, lecturers, and students. The results show that key challenges include limited marketing communication resources, weak integration of entrepreneurial values into promotional messages, and low public awareness of vocational education advantages. External challenges also stem from public perceptions that favor academic universities over polytechnics. Theoretically, this research contributes to higher education branding literature by applying the DRIP Model (Differentiate, Reinforce, Inform, Persuade) to vocational entrepreneurship education. Practically, it offers strategic insights for vocational institutions to design consistent, value-based communication strategies that strengthen competitiveness and stakeholder engagement.